2020
DOI: 10.1093/tas/txaa081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of energy source and level, animal age, and sex on the flavor profile of sheep meat12

Abstract: The effects of dietary energy source, energy level, sheep age, and sheep sex on flavor and off-flavor intensity were evaluated. Consumer panelists, with previous lamb-eating experience, assessed lamb flavor and off-flavor intensity on a 100-point, end-anchored scale (0 = very mild to 100 = very intense), with off-flavor being defined as anything different than lamb flavor. Lamb longissimus thoracis (LT) and whole, boneless ground shoulder (GS) formed into patties were evaluated. Trial 1 was a randomized comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
(43 reference statements)
0
4
0
2
Order By: Relevance
“…In agreement with the present study, Jeremiah et al (1998) reported that generally lamb flavor intensity of boneless shoulder roasts increased with advancing age (3 to 15 mo) and harvest weight (31.8 to 76.8 kg) of sheep. Additionally, Jaborek et al (2020) reported a numerically greater lamb flavor and off-flavor intensity with increasing age between lambs, yearlings, and mature ewes, and a greater lamb flavor and off-flavor intensity for older, heavy weight, long-fed lambs compared with younger, typical market weight lambs. Using subcutaneous fat samples from sheep in the study conducted by Jaborek et al (2020) , Castada et al (2017) reported that a greater concentration of 3-methylindole (skatole), 4-methyloctanoic acid, 4-methylnonanoic acid, and 4-ethyloctanoic acid corresponded with a greater lamb flavor intensity rating.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In agreement with the present study, Jeremiah et al (1998) reported that generally lamb flavor intensity of boneless shoulder roasts increased with advancing age (3 to 15 mo) and harvest weight (31.8 to 76.8 kg) of sheep. Additionally, Jaborek et al (2020) reported a numerically greater lamb flavor and off-flavor intensity with increasing age between lambs, yearlings, and mature ewes, and a greater lamb flavor and off-flavor intensity for older, heavy weight, long-fed lambs compared with younger, typical market weight lambs. Using subcutaneous fat samples from sheep in the study conducted by Jaborek et al (2020) , Castada et al (2017) reported that a greater concentration of 3-methylindole (skatole), 4-methyloctanoic acid, 4-methylnonanoic acid, and 4-ethyloctanoic acid corresponded with a greater lamb flavor intensity rating.…”
Section: Resultsmentioning
confidence: 90%
“…Additionally, Jaborek et al (2020) reported a numerically greater lamb flavor and off-flavor intensity with increasing age between lambs, yearlings, and mature ewes, and a greater lamb flavor and off-flavor intensity for older, heavy weight, long-fed lambs compared with younger, typical market weight lambs. Using subcutaneous fat samples from sheep in the study conducted by Jaborek et al (2020) , Castada et al (2017) reported that a greater concentration of 3-methylindole (skatole), 4-methyloctanoic acid, 4-methylnonanoic acid, and 4-ethyloctanoic acid corresponded with a greater lamb flavor intensity rating. The concentration of branched-chain fatty acids, 4-methyloctanoic acid, 4-methylnonanoic acid, and 4-ethyloctanoic acid, which are responsible for the species-specific flavor of sheep meat, also increase with advancing animal age ( Watkins et al, 2010 ) and may be the reason for the findings in the present study.…”
Section: Resultsmentioning
confidence: 90%
“…Referente al sabor de la carne de ovino, en la bibliografía especializada se ha establecido el término "pastoral flavour", que se traduce como "sabor a pasto", para definir un sabor característico que, a veces, se presenta en la carne de rumiantes de edad avanzada criados en pastoreo o con alto contenido en forraje en la dieta (Schreurs et al, 2008). En este sentido, Jaborek et al (2020) mencionaron que el contenido de ácidos grasos de cadena ramificada, de entre 8 y 10 carbonos, está directamente relacionado con el olor fuerte a ovino, el cual se incrementa conforme avanza la edad de los animales.…”
Section: Edadunclassified
“…Current studies have shown that “mutton flavor” comes particularly from subcutaneous adipose tissue, and that 4-Methyl-8:0, 4-Ethyl-8:0, and 4-Methyl-9:0 are the three main branched-chain fatty acids responsible for conferring the species-specific flavor in sheep [ 90 , 91 ]. Based on this, studies on the taste of goats and sheep, have sought to score consumers’ taste intensity preferences [ 92 ].…”
Section: Application Of Goat and Sheep By-products To Obtain New Ingr...mentioning
confidence: 99%
“…Further research revealed that in male goats, the 4-Et 8:0 fatty acid was specifically associated with goat aroma [ 93 ], and the same fatty acid was identified in both sheep and goat meat [ 60 ]. Since then, several studies have shown that these fatty acids negatively affect the taste of goat meat [ 60 , 91 , 94 ].…”
Section: Application Of Goat and Sheep By-products To Obtain New Ingr...mentioning
confidence: 99%